2021
DOI: 10.3389/fnagi.2021.706282
|View full text |Cite
|
Sign up to set email alerts
|

The Screening Accuracy of a Visually Based Montreal Cognitive Assessment Tool for Older Adult Hearing Aid Users

Abstract: ObjectivesThis research aims to validate a modified visually based Montreal Cognitive Assessment for hearing-aid users (MoCA-HA). This population should be the target of cognitive screening due to high risk of developing dementia.DesignCase-control study.SettingThe participants were recruited from referral hearing-aid center and memory clinic in central London, United Kingdom.Participant75 hearing-aid users were recruited. Of these, thirty were cognitively intact controls with hearing impairment (NC-HI); thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This result is in line with the results of MacDonald et al ( 2012 ) study, which noted significant improvements in the MMSE after hearing augmentation in the elderly. Hence, a modified visually cognitive assessment and its cutoff point should be validated for cognitive tests in the population with hearing loss (Utoomprurkporn et al, 2021 ). As for the disagreements among the sub-domains of cognition, the characteristics of each tool and different aspects of cognitive function might be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the results of MacDonald et al ( 2012 ) study, which noted significant improvements in the MMSE after hearing augmentation in the elderly. Hence, a modified visually cognitive assessment and its cutoff point should be validated for cognitive tests in the population with hearing loss (Utoomprurkporn et al, 2021 ). As for the disagreements among the sub-domains of cognition, the characteristics of each tool and different aspects of cognitive function might be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the assessment mode of most commonly used cognitive tools is auditory based, which may hinder the hearing-impaired population responses. Therefore, our result suggested that visually based cognitive screening tools may also be considered when assessing the hearing-impaired population ability (Utoomprurkporn et al, 2021b). It may unveil their compensated cognitive ability via other means such as visuospatial found in our cohort.…”
Section: Rey Osterrieth Complex Figure Test Copymentioning
confidence: 66%
“…Therefore, we opted for the visually based MoCA to accurately assess the cognitive abilities of the hearing impaired participants. The detailed description of the test instruction and materials can be found in our previously published paper (Utoomprurkporn et al, 2021b).…”
Section: Montreal Cognitive Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison with the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) and the Mini Mental Status Examination (MMSE) showed that the computerized MoCA-HI correlated with the CERAD plus battery ( 38 ). Utoomprurkporn et al (2021) tested a modified version of Lin et al's computerized visual MoCA in 75 hearing aid users ( 39 ), 30 cognitive healthy, 30 with MCI and 15 with a clinical diagnosis of dementia reporting good sensitivity and specificity for MCI and dementia in their analysis. However, the small sample size and group differences in age and educational level limit the reliability of sensitivity/specificity estimates.…”
Section: Discussionmentioning
confidence: 99%